Impact of Value Education in Personal Behaviour of Students: A Case Study of Nepal - Shrestha, Bharat Kumar; Gupta, Pooja (Nepal Journal of Multidisciplinary Research, 2019)
Values are certain characteristics which affect the behaviour and characters of an individual. Values are a kind of standard principles that are used to judge the worth of an idea or action. They provide the criteria by which we decide whether something is good or bad, right or wrong. Values are taught by the value education of school. In Nepal, there is separate course of value education in basic education (grade 6 to 8). The main aim of this study was to explore the impact of value education in personal behaviour of students. The study was conducted in three districts (Dolkha, Kavre and Chitwan) of Nepal among the 600 students and teachers. The study was based on the quantitative approach. The result shows that the value education had taught basic qualities of life like Honesty, hard work, respect for others, cooperation, compassion, and forgiveness. It has brought the positive change in personal behaviour of students. Though, they reported the need of improvement in teaching practices because there was significant difference between the importance level and practice level of value education to teach the quality of life to change in personal behaviour.